Kepatuhan Wajib Pajak Orang Pribadi Ditinjau dari Fiscal Knowledge, Locus of Control, dan Interaksi antara Fiscal Knowledge dengan Locus of Control - Fransisca, Ika (Graduate School, Widya Mandala Catholic University Surabaya, 2011)
Indonesia adopts a self assessment that requires an awareness and volunteerism taxpayer in carrying out tax obligations. To support the success f this system, taxpayer compliance is absolutely necessary. These various factors shown to affect the level of tax compliance, such as age, gender, level of education, the income, or employment status, the influence of friends or other taxpayer, ethics, taxation sanctions, complexity, relationship with the lax authorities, income sources, an understanding of the quality taxation system, the possibility of tax audit and tax rates, knowledge/understanding of tax. This research reinforces previous research conducted by Groenland and Veldhoven (1983) to determine differences in individual taxpayer compliance in Surabaya in terms of fiscal knowledge, locus of control, and the interaction of both. Anticipated differences in fiscal knowledge, locus of control orientation, and interaction both able to explain the differences compliance WPOP in Surabaya and surrounding areas. One hundred and fifty questionnaires were distributed to a number of WPOP in Surabaya and surrounding areas. Of the 150 questionnaires were only 82 questionnaires that can be processed further. By using statistical analysis tools Kruskal Wallis non-parametric, this study .failed to reject the null hypothesis for all of the proposed hypothesis, which means there is no difference in the level of compliance WPOP Surabaya based fiscal knowledge, locus of control, and the interaction of both. The difference results of this study with previous studies because the majority of the answers WOP were obedient and almost all respondents have an internal locus of control. Keywords: Tm Compliance, Locus Of Control, Fiscal Knowledge.